Making sense of language in the light of evolution. (14th November 2017) - Bolhuis, Johan J.
Abstract : Inquiry into language evolution has been controversial, mainly because there is no consensus as to the nature of both 'evolution' and 'language.' Berwick and Chomsky make sense of the evolution of language by treating it as a biological phenomenon. In contrast to functional characterizations of language as 'communication' or 'speech, ' the authors define it as, essentially, a mind‐internal computational mechanism. Within their minimalist approach, hierarchical syntactic structure is achieved through the recursive application of a basic operation called ' Merge .' The simplicity of the basic operation is consistent with archeological evidence suggesting an evolutionary recent origin of language.